ANALYSIS AND GENERALIZATION OF REGULATORY SUPPORT FOR GEODESIC SUPPORT OF ROAD CONSTRUCTION OBJECTS: Array - Batrakova, A.; Dorozhko, Y.; Zakharova, E.; Kliuka, O. (Municipal economy of cities. Series: «Economy science», 2021)
The transfer of the project to the site requires the performance of measurements and constructions with high accuracy. Changes in the technology of geodetic works related to the computerization of geodesy, the introduction into geodetic practice of electronic geodetic instruments and automated processing programs, require the introduction into production of both traditional methods of geodetic measurements and new technologies and methods of geodetic works. Despite the fact that geodetic works are an integral part of construction, in the regulations on surveys, design and construction of roads and man-made structures quite limited regulation of the content of work on the transfer of projects to the field, division work, executive surveys, geodetic quality control, accuracy requirements, etc. Given the current state of regulatory and legal support for geodetic support of road construction sites, it is advisable to develop a national standard for the implementation of geodetic surveying and geodetic control in the construction of road construction sites. This standard will supplement the main provisions of regulations on the construction of roads and transport facilities. With the growing volume of design, construction and overhaul of roads, it is necessary to standardize all stages of design and construction work, including those related to geodetic production. The development of technologies and methods of geodetic works related to the computerization of geodesy requires the introduction into production of both traditional methods of geodetic measurements and new technologies and methods of geodetic works. Based on the analysis and generalization of regulatory support for geodetic support of design and construction of roads and artificial structures, the need to develop a national standard for geodetic surveying and geodetic control in the construction of road construction as a supplement to the basic provisions of regulations on road construction and transport facilities.